2006
DOI: 10.1158/0008-5472.can-05-1628
|View full text |Cite
|
Sign up to set email alerts
|

Protein 4.1B/Differentially Expressed in Adenocarcinoma of the Lung-1 Functions as a Growth Suppressor in Meningioma Cells by Activating Rac1-Dependent c-Jun-NH2-kinase Signaling

Abstract: Meningiomas are the second most common brain tumor in adults, yet comparatively little is presently known about the dysregulated growth control pathways involved in their formation and progression. One of the most frequently observed genetic changes in benign meningioma involves loss of protein 4.1B expression. Previous studies from our laboratory have shown that protein 4.1B growth suppression in meningioma is associated with the activation of the c-Jun-NH 2 -kinase (JNK) pathway and requires localization of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…DAL-1 forms a functional complex with CASPR2. This complex is thought to be involved in cell signaling through the activation of c-Jun amino-terminal kinase, a regulator of the retinoblastoma protein (Gerber et al, 2006). The mechanism of action of CASPR2 as a tumor suppressor gene may be similar to that of DAL-1.…”
Section: Discussionmentioning
confidence: 99%
“…DAL-1 forms a functional complex with CASPR2. This complex is thought to be involved in cell signaling through the activation of c-Jun amino-terminal kinase, a regulator of the retinoblastoma protein (Gerber et al, 2006). The mechanism of action of CASPR2 as a tumor suppressor gene may be similar to that of DAL-1.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms by which 4.1B promotes apoptosis remain unclear, one study recently showed that overexpression of 4.1B increases caspase-8 activity in MCF-7 cells (14). Others have reported that overexpression of 4.1B induces Rac1-dependent JNK signaling (13). Recent work from our laboratory has also shown that 4.1B can interact with a potential tumor suppressor, integrin ␤8 (26), and this interaction has been confirmed in our PC-3 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 4.1B, or a truncated form of this protein (known as Deleted in Adenocarcinoma of the Lung-1), is frequently lost in brain, lung, and breast cancers, and that overexpression of 4.1B can inhibit the in vitro growth of tumor cell lines (9)(10)(11)(12)(13)(14). In some cases, growth suppression was associated with increased apoptosis.…”
mentioning
confidence: 99%
“…23 Downstream effects of protein 4.1B include activation of a JNK (c-Jun-NH2-kinase) protein, which results in reduced cell growth via decreased cyclin A expression and phosphorylation of the retinoblastoma protein. 16 Protein 4.1B has been shown to interact with the cell growth regulator protein 14-3-3. Although aggressive meningiomas show reduced levels of 14-3-3 expression, impaired 14-3-3 function has not been shown to affect protein 4.1B function, suggesting that alternative signaling pathways are present.…”
Section: Targeted Molecule Chemotherapeutic Agentsmentioning
confidence: 99%